Detailed archaeomagnetic study of a ceramic workshop at Kato Achaia: New directional data and archaeomagnetic dating in Greece. - Tema, E. (Bulletin of the Geological Society of Greece, 2013)
New archaeomagnetic results from two ancient kilns excavated at Kato Achaia, southern Greece, are presented. According to archaeological evidence, both kilns were part of a bigger ceramic workshop, probably used for the production of bricks or ceramics. Systematic archaeomagnetic sampling was carried out collecting 9 brick samples from the first kiln (KL3) and 12 brick samples from the second kiln (KL5). Magnetic mineralogy measurements have been carried out in order to determine the main magnetic carrier of the samples and to check their thermal stability. Standard thermal demagnetization procedures have been used to determine the archaeomagnetic direction registered by the bricks during their last firing. The direction of the Characteristic Remanent Magnetization (ChRM) has been obtained from principal component analysis and the kilns mean directions were calculated using Fisher statistics. The archaeomagnetic ages of both kilns were determined using the most recent developments in data elaboration and were calculated after comparison of the kilns declination and inclination with the reference curves produced by the SCHA.DIF.3K European regional geomagnetic field model. Dating results are in good agreement with archaeological evidence of the site and suggest that both kilns were in use during Hellenistic times.